Physicochemical characteristics of pulsed electrical field–sterilized sugarcane (Saccharum officinarum L.) juice with added ginger extract - Arie Febrianto Mulyadi; Sucipto Sucipto; Sumardi Hadi Sumarlan; Dina Wahyu Indriani; Rafika Arofatul Lama’ah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
This study aimed to investigate the effect of the voltage of the pulsed electric field (PEF) and ginger extract concentration on sugar cane juice's physicochemical and organoleptic quality. The experiments were carried out at voltages of 20 kV and 40 kV, and ginger extract concentrations of 2, 4, and 6%. The PEF with 40 kV and 6% ginger extract concentration resulted in the most efficient microbial reduction by 99.54%. Sugarcane juice has a total number of microbes of 3.7x103 CFU/ml, antibacterial activity 1.48, pH of 6.26, total solids dissolved of 20.5 °Brix, a viscosity of 4.67 Cp, reducing sugar of 2.17%, brightness of 24.4, redness of 7.17, and yellowness of 8.1. The combination of pulsed electric field and ginger extract addition can preserve the shelf life and maintain sugarcane juice quality. The higher the PEF voltage and ginger extract concentration, the longer the quality of the sugarcane juice can be preserved.